A Hubble Instrument Comes Home: UW-Madison’s High Speed Photometer - Lattis, James (Proceedings of the Wisconsin Space Conference, 2012)
WSGC provided generous support to return the High Speed Photometer (HSP) to Wisconsin to be used for public education and outreach at UW Space Place. HSP was one of the original five science instruments built for and launched with the Hubble Space Telescope (HST). Declared to be federal surplus equipment in autumn 2011, HSP was acquired by UW Space Place and brought to Madison to be put on exhibit and used for public education. As the only research photometer built specifically for HST, HSP is an important part of the history of astronomical instrumentation and one of the most important astronomical instruments to come from Wisconsin.Â